Health professional assisted Kangaroo mother care practice in Ethiopian health care facilities: evidence from the 2016 Ethiopian demographic and health survey - Mesfin Wudu Kassaw; Ayele Mamo Abebe; Biruk Beletew Abate; Ayelign Mengesha Kassie; Kirubel Dagnaw Tegegne (BMC Pediatrics, 2023)
Abstract Background Worldwide, 15 million children born prematurely every year and over one million of them died because of prematurity caused complications. However, three-fourths of deaths from preterm related complications are preventable by using Kangaroo Mother Care (KMC). The Ethiopian government has been implementing a guideline that declares putting all low birth weight neonates at KMC. The aim of this study was to assess health professionals’ assisted KMC practice and its associated factors among Ethiopian mothers who gave birth at health facilities. Methodology This study used the 2016Ethiopian Demographic and Health Survey data (EDHS). The 2016EDHS used a stratified two stage sampling method to select a representative sample using validated questioner. The sample we used in this study after cleaning the children’s data set from the 2016EDHS was 2,960. Logistic regression model was used to assess the association of health professional assisted KMC practice and predictor variables. Results Mothers who gave birth in health facilities and practiced kangaroo mother care were 1808(62.1%). In the multivariable logistic regression analysis, women from poorest (AOR, (95%CI)), (0.60, (0.43, 0.81)) and poorer (0.62, (0.46, 0.86)) socio-economic status were not practicing KMC. Conclusions The coverage of health professional assisted KMC practice was far lower than the expectation for mothers who gave birth in health facilities (100%). Low socio-economic status was associated with not practicing KMC. A further study on why mothers from low wealth index did not practicing KMC while they were in health facilities may be needed.